Study of mechanical behaviour of eulaliopsis binata fiber reinforced polymer composite. (2019) - Acharya, Samir Kumar; Pradhan, Subhrajit
Abstract: In this investigation a new unexplored potential non-wood natural fiber, eulaliopsis binata (short fiber) is taken as reinforcement with epoxy as matrix material to examine the potential of the fiber as a reinforcement material. The incorporation of short eulaliopsis binata (sabai) fiber with different weight percentage (5, 10, 20, 30, 40) contributed towards enhancement of the mechanical properties of the composite. The modulus of elasticity, modulus of rupture, impact strength, hardness was found to be optimum for the composite with 30% weight fraction of fiber. The addition of fiber beyond 30% fiber fraction leads to fiber agglomeration, poor bonding at fiber matrix interface causing deterioration of mechanical strengths of the composite. The SEM analysis reveals fiber pullout, fiber-matrix debonding, micro crack propagation is found to be some of the primitive causes for the failure of composite under study.